A new design of cellular soft continuum manipulator based on beehive-inspired modular structure. (2nd June 2017) - Meng, Cai; Xu, Weidong; Li, Haiyuan; Zhang, Huan; Xu, Dong
In this article, a design of honeycomb structure–based soft continuum manipulator is proposed to achieve higher structural strength while keeping compact layout, low material consumption, and thinner wall. At first, a pneumatic deformable cell is designed to simulate the beehive hexagon structure. Secondly, cell units are combined together in a parallel way to form the body module whose stiffness is increased. Thirdly, a gripper module is designed based on the combination of the cell units in one end. Fourthly, several body modules and a gripper module are serially linked to form a soft robot. Fifthly, the basic kinematics of the module is modeled and analyzed. Finally, a prototype made up of silicone rubber is developed for experiments. In the experiments, the soft robot managed to pick up a ball and an egg. The quantitative experiments show that the maximum bending angle was about 90°, and the maximum extending ratio approaches 1.7:1 for a three-module robot test. Reliability test shows a good behavior even though the robot lost its 50% cells. The results show that the new design idea, which is inspired by the cell in biology, is available to improve the reliability of soft robot as expected and enables the robot to move with good flexibility.